2018
DOI: 10.1177/0020852317748730
|View full text |Cite
|
Sign up to set email alerts
|

Do audit firm and audit costs/fees influence earnings management in Swedish municipalities?

Abstract: Previous research on the private sector shows that auditors and auditing firms are important actors in ensuring high-quality reporting based on accrual accounting. The aim of this study is to explore whether audit firms and audit costs/fees influence municipalities' probability of applying earnings management in their annual accounts. The empirical data, which covered the financial years 2011-2013, were handpicked from annual reports or retrieved from other sources. In general, our study shows that the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 56 publications
1
37
1
1
Order By: Relevance
“…Empirical evidence on the relationship between audit fees and earnings management is mixed (Lin and Hwang, 2010). Several studies confirm the first argument regarding the existence of a positive relationship between audit fees and earnings management (Gul et al, 2003;Antle et al, 2006;Choi et al, 2010;Alali, 2011;Sharma et al, 2011;Gu and Hu, 2015;Donatella et al, 2018), whereas other studies support the second argument and document a negative association between them (Frankel et al, 2002;Srinidhi and Gul, 2007). Finally, some studies found that there is no association between audit fees and earnings management (Ashbaugh et al, 2003;Chung and Kallapur, 2003).…”
Section: Audit Fees and Earnings Managementmentioning
confidence: 99%
“…Empirical evidence on the relationship between audit fees and earnings management is mixed (Lin and Hwang, 2010). Several studies confirm the first argument regarding the existence of a positive relationship between audit fees and earnings management (Gul et al, 2003;Antle et al, 2006;Choi et al, 2010;Alali, 2011;Sharma et al, 2011;Gu and Hu, 2015;Donatella et al, 2018), whereas other studies support the second argument and document a negative association between them (Frankel et al, 2002;Srinidhi and Gul, 2007). Finally, some studies found that there is no association between audit fees and earnings management (Ashbaugh et al, 2003;Chung and Kallapur, 2003).…”
Section: Audit Fees and Earnings Managementmentioning
confidence: 99%
“…In line with previous studies in the Swedish setting, size is measured as the natural logarithm of residents in each municipality (e.g. Collin et al 2017;Donatella et al 2019).…”
Section: Sizementioning
confidence: 99%
“…While the driving force of municipalities is not profit, but continuity, earnings management is used to present financial results of zero, to indicate the capacity of local politicians to keep the level of costs in line with income (Cohen et al, ; Ferreira, Carvalho, & Pinho, ). Research indicates that the adoption of legal provisions, for instance, IFRS, will not automatically reduce earnings management in the banking industry and the same holds probably true for municipalities (Donatella, Haraldsson, & Tagesson, ; van Oosterbosch, ). Moreover, it can be argued that the implementation of an accrual accounting system provides more possibilities to engage in forms of earnings management, instead to provide a reliable, true, and fair view of the overall financial situation of the accounting entity (Vinnari & Näsi, , p. 112, Cohen et al, ).…”
Section: Further Exploration and Analysismentioning
confidence: 99%
“…Controllers do experience political and managerial pressure to manipulate costs in order to demonstrate that public spending is in line with income and in order to safeguard budgets for spending next year. While earlier studies focused on the valuation of assets and the external accounting function (Donatella et al, ; Reischmann, ; Vinnari & Näsi, ), the object of this study is the imputation of expenses by internal controllers. Moreover, while earlier studies on earnings management focus on electoral motives, the motivation for earnings management could be more bureaucratic.…”
Section: Further Exploration and Analysismentioning
confidence: 99%